2013
DOI: 10.1002/jcc.23329
|View full text |Cite
|
Sign up to set email alerts
|

A parallel finite element simulator for ion transport through three‐dimensional ion channel systems

Abstract: A parallel finite element simulator, ichannel, is developed for ion transport through three-dimensional ion channel systems that consist of protein and membrane. The coordinates of heavy atoms of the protein are taken from the Protein Data Bank and the membrane is represented as a slab. The simulator contains two components: a parallel adaptive finite element solver for a set of Poisson-Nernst-Planck (PNP) equations that describe the electrodiffusion process of ion transport, and a mesh generation tool chain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 55 publications
(52 reference statements)
1
56
0
1
Order By: Relevance
“…45 leads to a nonlinear weak form. Similar weak forms and the bilinear forms for FEM to solve the SMPNP have been presented explicitly in our former work [62,63]. To deal with the nonlinearity of the weak form of Eq.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…45 leads to a nonlinear weak form. Similar weak forms and the bilinear forms for FEM to solve the SMPNP have been presented explicitly in our former work [62,63]. To deal with the nonlinearity of the weak form of Eq.…”
Section: Methodsmentioning
confidence: 92%
“…To deal with the nonlinearity of the weak form of Eq. 45, we use Newton method to linearize the system as given in previous work [62,63]. Also, relaxation iteration is employed to obtain convergent simulation results for the coupled PDE systems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work [32], we have already shown that the mesh generated by TMSmesh can be successfully applied to BEM calculations with better convergence performance and lead to reasonable results. The volume tetrahedral mesh generated from the TMSmesh surface mesh by the tool chain described in this review also show good performance in the usage of FEM computations [38].…”
Section: Application Of Molecular Surface Mesh To Bem and Fem In Contmentioning
confidence: 88%
“…A widely used continuum model for simulating ionic transport is based on the Poisson-Nernst-Planck (PNP) equation [9,12]. A number of numerical algorithms including finite difference [13,14], finite element [15][16][17][18][19], spectral element [20], and finite volume methods [21] have been utilized in the past two decades to solve the PNP equation. The finite element method has the advantage of handing complex geometries and curved boundaries.…”
Section: Introductionmentioning
confidence: 99%